Role of the focus of attention in the treatment of generalized social phobia in adolescents - Amorós Boix, Maravillas; Rosa Alcázar, Ana Isabel; Olivares Olivares, Pablo J. (Anales de Psicología / Annals of Psychology, 2011)
The aim of this experimental study is to analyze the relative efficacy of attention training in cognitive-behavioral treatment “Intervención en Adolescentes con Fobia Social”(IAFS; Olivares, 2005). Fifty-three spanish adolescents 15.90 years old average (13-17 rank) and majority women (86.79%) meeting Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR, 2002) criteria for Social Phobia were randomly assigned to IAFS multicomponent package (IAFS from here) or IAFS without focused attention (IAFS without FA from here). None had been psychological treatment before and 92.3% had not any relative with any psychological disorder. The results show nonsignificant differences between the two experimental conditions, being both equal before the treatment begins and according to specific measures assessing anxiety and avoidance as well as other related constructs (assertiveness, self-esteem and adjustment). In general, although attention training could potentiate greater treatment benefits, compared to IAFS without FA, IAFS does not significant improve outcomes.